Spatiotemporal control of endocytosis by phosphatidylinositol-3,4-bisphosphate - Posor, York; Eichhorn-Gruenig, Marielle; Puchkov, Dmytro; Schöneberg, Johannes; Ullrich, Alexander; Lampe, André; Müller, Rainer; Zarbakhsh, Sirus; Gulluni, Federico; Hirsch, Emilio; Krauss, Michael; Schultz, Carsten; et al. (Nature, 2013)
Phosphoinositides are important regulators of intracellular membrane traffic, and although the role of PI(4,5)P2 has been well characterised, the function of PI(3,4)P2 remains unclear; here the formation of PI(3,4)P2 by the class II phosphatidylinositol-3-kinase C2α enzyme is shown to control clathrin-mediated endocytosis.